2021
DOI: 10.1111/1759-7714.14191
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0016760 accelerates non‐small‐cell lung cancer progression through miR‐646/AKT3 signaling in vivo and in vitro

Abstract: Background Currently, the prognosis of non‐small‐cell lung cancer (NSCLC) patients remains dismal due to recurrence and metastasis. The purpose of our study was to explore the role of circular RNA_0016760 (circ_0016760) in NSCLC progression and its associated mechanism. Methods Quantitative real‐time polymerase chain reaction (qRT‐PCR) was implemented to measure the expression of circ_0016760, microRNA‐646 (miR‐646) and AK strain thymoma serine/threonine kinase 3 (AKT3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Genome wide analysis has also demonstrated that circRNAs are evolutionary conserved among species 32 , 33 . In the field of cancer biology, circRNAs have been found to significantly impact tumor cell growth 34 - 36 , proliferation 37 , 38 , invasion 39 - 41 , adhesion 42 , 43 , metastasis 44 - 47 and apoptosis 48 , 49 , suggesting their potential to be used as diagnostic and prognostic biomarkers, as well as therapeutic agents 50 - 52 .…”
Section: Regulation Of Hippo-yap Signaling Axis By Circrnasmentioning
confidence: 99%
“…Genome wide analysis has also demonstrated that circRNAs are evolutionary conserved among species 32 , 33 . In the field of cancer biology, circRNAs have been found to significantly impact tumor cell growth 34 - 36 , proliferation 37 , 38 , invasion 39 - 41 , adhesion 42 , 43 , metastasis 44 - 47 and apoptosis 48 , 49 , suggesting their potential to be used as diagnostic and prognostic biomarkers, as well as therapeutic agents 50 - 52 .…”
Section: Regulation Of Hippo-yap Signaling Axis By Circrnasmentioning
confidence: 99%
“…Earlier or more sensitive biomarker to diagnose CRC is very good for CRC patients (Yang et al 2017). A growing number of studies have shown that circRNAs were significantly dysregulated and had a very important regulatory role in many diseases, such as hepatocellular carcinoma (Chen et al 2021c), cardiovascular disease , non-small-cell lung cancer (Chen et al 2021b), prostate cancer (Mugoni et al 2021) and breast cancer (Wu et al 2021). In our study, we determined the expression of circ_0001821 in CRC tissues and its cell lines, and investigated more deeply the biological function of circ_0001821 played in CRC development.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-mimics, miR-7 mimics, miR-inhibitor, and miR-7 inhibitor were obtained from RiboBio Company (RiboBio, Guangzhou, China). When cell confluence reached about 70%, Lipofectamine 3000 reagent (Sigma Aldrich, USA) was applied to transfect cells according to the supplier’s procedures (Chen et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%